An improved bioassay to study arabidopsis induced systemic resistance (ISR) against bacterial pathogens and insect pests - Cecchini, Nicolas Miguel (2019)
The plant immune system is essential for plants to perceive and defend against bacterial, fungal and insect pests and pathogens. Induced systemic resistance (ISR) is a systemic immune response that occurs upon root colonization by beneficial microbes. A well-studied model for ISR is the association of specific beneficial strains of Pseudomonas spp. with the reference plant Arabidopsis thaliana. Here, we describe a robust, increased throughput, bioassay to study ISR against the bacterial pathogen Pseudomonas cannabina pv. alisalensis (formerly called Pseudomonas syringae pv. maculicola) strain ES4326 and the herbivore Trichoplusia ni by inoculating Pseudomonas simiae strain WCS417 (formerly called Pseudomonas fluorescens WCS417) on Arabidopsis plants grown in Jiffy-7® peat pellets. While most commonly used for Pseudomonas-triggered ISR on Arabidopsis, this assay is effective for diverse rhizosphere bacterial strains, plant species, pathogens and herbivores.